Contested Landscapes: Territorial Conflicts and the Production of Different Ruralities in Brazil - Fernandes, Bernardo Mançano [UNESP]; Welch, Clifford Andrew (Springer Nature, 2022)
It is through landscape that we see and feel the complexity of the relations and objects that make up space, territory, region, and place. Landscape is the expression of the multidimensionality and multiscalarity of territory and its ruralities (Marsden, Sociologia Ruralis 29:312–317, 1989). In rural studies landscape is made manifest by rurality. Rurality is the configuration of social life in relation to natural resources, goods, services, cultural values, and social categories like class—the social formation, as it were—of the territories that make up rural landscapes (Hecht, Land Use Policy 27:161–169, 2010; Wanderley, Estudos Sociedade e Agricultura 15:87–145, 2000).